Analysis of Endocan Levels in Hypertensive Patients as Risk Factors of Chronic Kidney Disease - Suryani Jamal; Uleng Bahrun; Ibrahim Abdul Samad; Fitriani Mangarengi; Hasyim Kasim; Ilham Jaya Patellongi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
This study aimed to analyze endocan levels as a marker of endothelial dysfunction in the control group, patients withstage I hypertension, stage II hypertension, and patients with end-stage renal disease. Endocan levels were measured withESM-1 (endocan) kit by Enzyme-Linked Immunosorbent Assay (ELISA) method. This study used a cross-sectional methodand was conducted in Dr. Wahidin Sudirohusodo Hospital, Makassar and Hasanuddin University Hospital from Septemberto October 2017. There were 83 samples in this study, consisting of 12 samples in the control group, 22 samples of stage Ihypertension, 28 samples of stage II hypertension, and 21 samples of end-stage renal disease aged 20-90 years old. Thisstudy showed significantly higher endocan levels in patients with stage II hypertension and end-stage renal disease(p< 0.05). Endocan levels were significantly higher (p<0.05) in patients with end-stage renal disease compared with thecontrol group and patients with stage I hypertension; but not significantly higher (p > 0.05) compared to patients with stageII hypertension. Also, the median of endocan levels in patients with the end-stage renal disease was higher (309,850 ng/L)compared to patients with stage II hypertension (273,050 ng/L).